CeO2/Bi2WO6 Heterostructured Microsphere with Excellent Visible‐light‐driven Photocatalytic Performance for Degradation of Tetracycline Hydrochloride. (9th May 2017) - Zhang, Fengjun; Zou, Shuang; Wang, Tianye; Shi, Yuxi; Liu, Peng
Abstract: CeO2 /Bi2 WO6 heterostructured microsphere with excellent and stable photocatalytic activity for degradation tetracyclines was successfully synthesized via a facile solvothermal route. The photocatalytic experiments indicated that CeO2 /Bi2 WO6 heterostructured microspheres exhibited enhanced photocatalytic activity compared to pure Bi2 WO6 in both the degradation of tetracycline hydrochloride (TCH) and rhodamine B (RhB) under visible‐light irradiation. The 1CeO2 /2Bi2 WO6 exhibited the best photocatalytic activity for degradation of TCH, reaching 91% after 60 min reaction. The results suggested that the particular morphological conformation of the microspheres resulted in smaller size and more uniform morphology so as to increase the specific surface area. Meanwhile, the heterojunction was formed by coupling CeO2 and Bi2 WO6 in the as‐prepared microspheres, so that the separation efficiency of photogenerated electrons and holes was dramatically improved and the lifetimes of charge carriers were prolonged. Hence, introduction of CeO2 could significantly enhance the photocatalytic activity of CeO2 /Bi2 WO6 heterostructured microspheres and facilitate the degradation of TCH. This work provided not only a principle method to synthesize CeO2 /Bi2 WO6 with the excellent photocatalytic performance for actual produce, but also a excellent property of the photocatalyst for potential application in photocatalytic treatment of tetracyclines wastewater from pharmaceutical factory. Abstract : Schematic diagram of charge separation in visible‐light irradiation and the energy band mechanism of enhanced photocatalytic activity of CeO2 /Bi2 WO6 heterostructured microspheres.